The msaABCR Operon Regulates Persister Formation by Modulating Energy Metabolism in Staphylococcus aureus - Pandey, Shanti; Sahukhal, Gyan S.; Elasri, Mohamed O. (Frontiers in Microbiology, 2021)
Staphylococcus aureus is a major human pathogen that causes chronic, systemic infections, and the recalcitrance of these infections is mainly due to the presence of persister cells, which are a bacterial subpopulation that exhibits extreme, yet transient, antibiotic tolerance accompanied by a transient halt in growth. However, upon cessation of antibiotic treatment, a resumption in growth of persister cells causes recurrence of infections and treatment failure. Previously, we reported the involvement of msaABCR in several important staphylococcal phenotypes, including the formation of persister cells. Additionally, observations of the regulation of several metabolic genes by the msaABCR operon in transcriptomics and proteomics analyses has suggested its role in the metabolic activities of S. aureus. Given the importance of metabolism in persister formation as our starting point, in this study we demonstrated how the msaABCR operon regulates energy metabolism and subsequent antibiotic tolerance. We showed that deletion of the msaABCR operon results in increased TCA cycle activity, accompanied by increased cellular ATP content and higher NADH content in S. aureus cells. We also showed that msaABCR (through MsaB) represses the ccpE and ndh2 genes, thereby regulating TCA cycle activity and the generation of membrane potential, respectively. Together, the observations from this study led to the conclusion that msaABCR operon deletion induces a metabolically hyperactive state, leading to decreased persister formation in S. aureus.